POLYCYSTIC OVARY SYNDROME IN WOMEN - Maripjonov Jasurbek Ma’mirjon o’g’li; Anvarova Mubinabonu Azizbek qizi; Mavlonova Surayyo Malikjon qizi (Journals Park Publishing, 2025)
This article discusses the causes of polycystic ovary syndrome (PCOS) in women and the methods of treatment for this condition. PCOS is an endocrine disorder characterized by menstrual cycle irregularities, hyperandrogenemia, and metabolic changes due to ovarian dysfunction. It is prevalent among women of reproductive age and significantly impacts reproductive health and metabolic status. PCOS is a complex endocrine-metabolic syndrome requiring long-term monitoring and comprehensive treatment. Timely diagnosis and treatment based on an individualized approach can help improve reproductive health and reduce metabolic risks.
Keywords: Hormonal changes, hormonal disorders, polycystic ovary syndrome, ovaries, menstrual cycle irregularities, infertility.